2019
DOI: 10.1108/ejmbe-08-2018-0088
|View full text |Cite
|
Sign up to set email alerts
|

Do Islamic stock indexes outperform conventional stock indexes? A state space modeling approach

Abstract: Purpose The purpose of this paper is to investigate whether Islamic stock indexes outperform conventional stock indexes, in terms of informational efficiency and risk, during the recent financial instability period. Design/methodology/approach The paper uses a state space model combined with a standard GARCH(1,1) specification while taking into account structural breakpoints. The authors allow for efficiency and volatility spillovers to be time-varying and consider break dates to locate periods of financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 40 publications
8
40
0
1
Order By: Relevance
“…Overall, these findings suggest that: (i) the stock returns of the conventional index are significantly negatively related to both daily growth in total confirmed cases and daily growth in total cases of death caused by COVID-19; (ii) faith-based investments/index are less exposed to the outbreak of COVID-19 than its conventional peer. These results are broadly comparable to the findings of Trichilli et al (2020a) and Rejeb and Arfaoui (2019) who found that Islamic indices are partially immune from speculative shocks to global financial services. Furthermore, they indicated that the ethical stock market indices perform much better during calm periods and moderately better during times of crisis; and Islamic asset allocation is safer during pandemics and economic periods and distress.…”
Section: Empirical Findingssupporting
confidence: 89%
“…Overall, these findings suggest that: (i) the stock returns of the conventional index are significantly negatively related to both daily growth in total confirmed cases and daily growth in total cases of death caused by COVID-19; (ii) faith-based investments/index are less exposed to the outbreak of COVID-19 than its conventional peer. These results are broadly comparable to the findings of Trichilli et al (2020a) and Rejeb and Arfaoui (2019) who found that Islamic indices are partially immune from speculative shocks to global financial services. Furthermore, they indicated that the ethical stock market indices perform much better during calm periods and moderately better during times of crisis; and Islamic asset allocation is safer during pandemics and economic periods and distress.…”
Section: Empirical Findingssupporting
confidence: 89%
“…For instance, the author studied the effect of US term premium on volatility of stock market and found that when variations in interest rates increase, investors might adjust their demands for risk compensations, thus we ought to see positive reaction in stock market volatility. Several other studies showed that Islamic stock markets remain slightly away from effects of financial instability and effects of the subprime crisis (Ben-Rejeb and Arfaoui, 2019;Arfaoui and Ben-Rejeb, 2017;Hammoudeh et al, 2014). Then aside from any corrective action, it is relatively plausible to pronounce that Islamic finance industry do not seem able to be in safeguard position against economic and financial shocks affecting international markets.…”
Section: Volatility Of Djim Equity Indicesmentioning
confidence: 99%
“…(Narayan & Bannigidadmath, 2017) says that a company issues shares and sells the rights of its own but only issues one class of common stock or often referred to as common stock. According to (Al-Khazali et al, 2014) suggests that shares are securities that state the asset income of a company.…”
Section: B Literature Reviewmentioning
confidence: 99%